Impact of COVID-19 on Youth's Lifestyle and Well-being: A Secondary Data Analysis - Sarker, Anupom (Journal of Community Health Provision, 2023)
It is widely recognized that the initial case of the coronavirus was identified in Wuhan City, Hubei Province, China, on December 31, 2019.  Following this, the World Health Organization officially classified it as a worldwide pandemic on March 11, 2020. Multiple studies have demonstrated that these pandemic affects individuals of all ages, although the incidence rate is lowest among young people. The global situation, however, has led to the observation of distinct effects within this group. The reason can be said that in many countries around the world, schools, colleges and universities are closed for a long time.  This changes the general lifestyle of the youth group. In this paper, the impact of Covid-19 on the lifestyle of youth groups is discussed. The impact of this virus has been seen to be more pronounced among the youth. Because of the impact, changes in their lifestyles have been found that have been dire. This study found that during Covid-19, youth spent more time sleeping than they normally would. During the pandemic, instead of using their study time, they have spent a lot of time on social media or various types of games. And, the positive impact is that Covid-19 is introducing young people as well as all students to the online education system. Badly the pandemic has a significant impact on the mental health of young people. On the other side, the pandemic has had a positive impact on the lives of young people in terms of hygiene.